SUKU SAKAI DALAM TIGA KEKUASAAN DI RIAU - Isdarwanto, Totok; Zulfa, Zulfa (Jurnal Ilmu Budaya, 2010)
This writing aim to describe the history of Sakai tribe and to portray Sakai tribe in the three periods: the periods Siak kingdom, Dutch colonization, and Japan colonizations.